2018
DOI: 10.1080/02786826.2018.1513636
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol size distribution measurement of electronic cigarette emissions using combined differential mobility and inertial impaction methods: Smoking machine and puff topography influence

Abstract: A combination of a real-time high resolution aerosol differential mobility spectrometer (DMS500) and an electrical low pressure impactor (used as a traditional impactor) was applied to simultaneously collect real-time data and analyze particle size by weighing the mass of the aerosol collected on the impactor stages. Nonrefillable fixed-power as well as refillable and power adjustable e-cigarettes (e-cigs) were tested at various puffing flow rates. Two types of smoking machines were used: a smoke cycle simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 49 publications
2
34
1
Order By: Relevance
“…All vaping pens are bottom type coils and were used in a vertical position to provide better coverage of the coils by the liquid. Because no puffing topography data relevant to VEA/THC vaping were available (Carrara, Giroud, and Concha-Lozano 2019), we applied a puffing regimen that was previously used for e-cigarette tests (Mikheev et al 2018). Eight squareshaped 5-s puffs with 60-s inter-puff intervals at a flow rate of 20 or 40 mL/s were performed per test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All vaping pens are bottom type coils and were used in a vertical position to provide better coverage of the coils by the liquid. Because no puffing topography data relevant to VEA/THC vaping were available (Carrara, Giroud, and Concha-Lozano 2019), we applied a puffing regimen that was previously used for e-cigarette tests (Mikheev et al 2018). Eight squareshaped 5-s puffs with 60-s inter-puff intervals at a flow rate of 20 or 40 mL/s were performed per test.…”
Section: Methodsmentioning
confidence: 99%
“…DMS500 provides count median diameter (CMD) measurements at high particle size resolution (38 size classes) within wide particle size and concentration ranges (5 nm to 1 mm, and up to 9 orders of magnitude, respectively). The Electrical Low Pressure Impactor (ELPIĆ¾; Dekati Ltd, Kangasala, Finland), which collects aerosol on 14 size fractions (6 nm to 10 mm), was applied simultaneously with DMS500 in a similar manner as described earlier (Mikheev et al 2018) for one of the test conditions (Joyetech eVic at 8.4 W heating power and 20 mL/s puffing flow rate) to sample aerosol on aluminum foils (placed on the impactor stages). Aerosol collected on the foils was used for gravimetric mass median aerodynamic diameter (MMAD) determination and then delivered for chemical analysis.…”
Section: Aerosol Size Distribution Characterizationmentioning
confidence: 99%
“…E-cig particles are primarily in the submicron size range (Fuoco et al 2014; Ingebrethsen, Cole, and Alderman 2012), exhibiting considerable differences in terms of size distribution ranging from a single mode to a tri-modal distribution reported by different studies (see Table S1 in the online supplementary information [SI]). Previous studies have also reported that the e-cig particle size distributions varied depending on e-cig puffing parameters (i.e., puffing flow rate, particle residence time, and the amounts of puffs) and environmental factors (i.e., temperature, relative humidity, and dilution factor) (Feng, Kleinstreuer, and Rostami 2015;Floyd et al 2018;Fuoco et al 2014;Manigrasso et al 2015;McAuley et al 2012;Meng et al 2017;Mikheev et al 2016;Mikheev et al 2018;Nguyen et al 2019;Schripp et al 2013;Scungio, Stabile, and Buonanno 2018;Sosnowski and Odziomek 2018;Wright et al 2016;Zervas et al 2018;Zhang, Sumner, and Chen 2013;Zhao et al 2016;Zhao et al 2017). However, limited studies have focused on the effects of e-liquid compositions on ecig particle size distribution, which is important for assessing exposure and related health effects.…”
Section: Introductionmentioning
confidence: 95%
“…Other authors proposed homemade systems to obtain PM from more easily accessible materials. In Ristovski's lab, cigarette and e-cigarette smoke was studied as an indoor particulate source [72,73]. In other works, various indoor deodorants, such as aroma diffusers, Armenian paper, incense, candles, and instant or automatic sprays, were used [74].…”
Section: Papapostolou Et Al Developed the Test Chamber Represented Inmentioning
confidence: 99%